Contracultura na New República: embates contra o neoliberalismo nas páginas da Chiclete com Banana (1985-1990) - Barros, Iberê Moreno Rosário e (2022)
The magazine Chiclete com Banana, published between 1985 and 1990, was one of the biggest success of Circo Editorial. Reaching the mark of over 100,000 sold copies, it figured as an important disseminator of new ideas and a booster to engage young people on debating. Playing as an arena for counterculture production, it was able to dialogue with different tribes, from beat poets and experimental theater actors, to marginal and underground movements such as the Punk’s. Constantly laying the idea of moral and good manners on the line and well-founded on the day-to-day life, the magazine managed to register the counterculture provocations at the time. Based on a theorical-methodological debate about the comics and using different pieces from diverse areas of humanities, which were mostly focused on political changes, specially those produced during or right after the political transition, the proposal here is to present the point of view of counterculture in order to understand Brazil’s redemocratization. That is the reason there had also been some theorical debates to make it possible to build definitions about neoliberalism and counterculture. This study investigates the magazine aiming at the following: get the connections between Circo Editorial – above all Angeli’s – and the Countercultural Movements (regarding the musical and theatrical scenario in Sao Paulo); understand the narrative clashes at the time, specially the opposition to the status quo; and, finally, as an specific goal, analyze the satirization of the neoliberal discourse present in the magazine. The ultimate objective is to prove that: The magazine Chiclete com Banana (1985-1990), stage for the counterculture in Brazil and opposition agent in the hegemonic dispute, was defeated by institutionalized politics and market